Schooling, educational achievement, and cognitive functioning among young Guatemalan adults - Stein, Aryeh D.; Behrman, Jere R.; DiGirolamo, Ann; Grajeda, Ruben; Quisumbing, Agnes R.; Ramakrishnan, Usha (SAGE Publications, 2005)
Quantity and quality of schooling obtained and the resulting skills and knowledge acquired are important components of human capital. We describe the distribution of selected measures of schooling, educational achievement, and cognitive functioning among individuals who participated as children in a nutrition supplementation trial in Guatemala and were followed up in 2002–04. Among 1,469 respondents (response rate 80%), who were 26–41 years of age in 2003, more than 90% of men and women had attended at least some school; more than half of men and more than one-third of women had completed sixth grade. Schooling attainment of both men and women has increased across birth cohorts but the schooling gap between men and women has increased. Parental socioeconomic status, as measured in 1975, is a strong predictor of schooling attainment. Basic literacy is high among those studied, with more than 80% able to read simple sentences. The gap in educational achievement favoring men narrowed across birth cohorts due to increases among younger women. The greater performance among men on the Raven's Progressive Matrices test persisted despite increased scores in the younger birth cohorts for both men and women. Migrants to Guatemala City have completed more years of school and scored higher on the tests of educational achievement and cognitive functioning than have cohort members who have remained in the study villages.